Translation Techniques of Culture Specific Items and Translation Ideology in Sarimin Webtoon - Putri, Astari Amalia; Rasyad, Himyar; Anggraini, Retno (English Department, Universitas Negeri Surabaya, 2023)
This research is an applied linguistic research in the translation field. The source chosen is an online comic or webtoon titled Sarimin by Nagaterbang. This research chooses Sarimin as the research subject because its theme heavily relies on Indonesian mysticism, making emphasis on several culturally specific items in the form of words, phrases, and sentences that are very hard to translate into English. There are three things studied in this research: (1) cultural terms in Sarimin, (2) translation techniques for the cultural terms, and (3) the translation ideology used in translating the cultural terms. The unit data are words, phrases, and sentences. The data are taken from the first season. The theoretical framework used in this analysis is the translation techniques from Molina and Albir (2002), Newmark's specific cultural terms (1988), and strategies of translation by Venuti (2001). From this study, it is found that the categories of cultural terms that appear most often are social culture with 39% with organizations, customs, and ideas items follows, not too far, with 35%. The study also found that the translator relied on adaptation which takes 41% of the items, and prioritizes domestication over foreignization. The analysis of the translation techniques reveals that many cultural elements cannot be translated as is and the chosen method may vary based on the context of the story. The findings highlight the need for translation guidelines to balance these two ideologies to preserve cultural richness while making the translation relatable to the target audience.